An Unusual Case of Left Atrial Mural Thrombus following Aortic Valve Replacement - Mohamed E. Taha; Ammar Eljack; Hisham Ibrahim; Chanwit Roongsritong (Case Reports in Cardiology)
The left atrial thrombus is a well-known complication of atrial fibrillation and rheumatic mitral valve disease and carries a high risk for systemic thromboembolism. They are generally dissolved after a certain period of optimal anticoagulation. A large thrombus, on the other hand, may persist even with adequate anticoagulation. The surgical removal of a thrombus theoretically poses some risk of systemic embolization, making its management a clinical dilemma. Furthermore, a refractory thrombus is uncommon. Thus, an evidence-based guideline in selecting the optimal therapy is needed. We report a case of a 74-year-old male with atrial fibrillation and a history of unprovoked pulmonary embolism who was incidentally found to have a massive left atrial thrombus shortly after discontinuing warfarin about 4 months following bioprosthetic aortic valve replacement. The thrombus was refractory to anticoagulation posing a clinical management dilemma. This case is interesting in terms of presentation and the approach to diagnosis and treatment.